2016
DOI: 10.1007/s10143-016-0761-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between endothelial nitric oxide synthase (eNOS) and natural history of intracranial aneurysms: meta-analysis

Abstract: The aneurysmal subarachnoid hemorrhage is a major public health problem described as a sudden drastic event with no warning symptoms and high morbidity and mortality rates. The role of the endothelial isoform of nitric oxide synthase gene polymorphism in intracranial aneurysms (IAs) is still a matter of controversy with divergent findings among European, American, and Asian populations. Our study purposed to test the association between intracranial aneurysms formation and nitric oxide gene polymorphisms throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 35 publications
0
13
0
1
Order By: Relevance
“…Endothelial cells express eNOS to serve as an important source of NO, a potent vasodilator and inhibitor of inflammation, platelet aggregation, and smooth muscle cell proliferation [ 42 ]. Interestingly, eNOS gene polymorphisms have been associated with vascular diseases [ 43 ]; two recent meta-analyses have identified the T786C polymorphism of eNOS as a predictor for the development of intracranial aneurysms in the cerebral vascular system [ 44 , 45 ], and various polymorphisms of eNOS have been linked to AAA [ 46 48 ]. Our findings of increased eNOS levels in larger aneurysms are in accordance with a recent animal study [ 49 ], in which increased eNOS activity reduced smooth muscle α-actin and upregulated MMPs during flow-induced intracranial aneurysm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells express eNOS to serve as an important source of NO, a potent vasodilator and inhibitor of inflammation, platelet aggregation, and smooth muscle cell proliferation [ 42 ]. Interestingly, eNOS gene polymorphisms have been associated with vascular diseases [ 43 ]; two recent meta-analyses have identified the T786C polymorphism of eNOS as a predictor for the development of intracranial aneurysms in the cerebral vascular system [ 44 , 45 ], and various polymorphisms of eNOS have been linked to AAA [ 46 48 ]. Our findings of increased eNOS levels in larger aneurysms are in accordance with a recent animal study [ 49 ], in which increased eNOS activity reduced smooth muscle α-actin and upregulated MMPs during flow-induced intracranial aneurysm formation.…”
Section: Discussionmentioning
confidence: 99%
“…9,63 Complementary studies of variants have also identified the presence of aneurysms as well as subsets of patients with aneurysms that are more likely to rupture, including tandem repeats in endothelial nitric oxide synthase (eNOS/NOS3) polymorphisms, with an OR as high as 11.4 (95% CI 1.7-75.9, p = 0.004) for individuals harboring 3 distinct variant alleles in this gene. 30,31,52 Further studies of eNOS polymorphic variants have suggested an association between rs2070744 and DCI following aSAH; however, these results only reached borderline significance (OR 2.936, 95% CI 1.048-8.226; p = 0.040). 24 Data from the same group also implicates a variant in HMGB1 in DCI (rs2249825: OR 5.695, 95% CI 1.804-17.975; p = 0.003).…”
Section: Genetic Modifiers Of Aneurysm Rupture and Subsequent Outcomesmentioning
confidence: 96%
“…NOS‐3 knockout predisposed mice subjected to unilateral carotid artery ligation to the formation of intracranial aneurysms (Abruzzo et al ., ). Single nucleotide polymorphisms (SNPs) in the eNOS gene are associated with the risk of developing IA in several populations (Yang et al ., ; Paschoal et al ., ).…”
Section: Vascular Protective Role Of Oestradiolmentioning
confidence: 97%